Thermodynamically stable amyloid-β monomers have much lower membrane affinity than the small oligomers - Sarkar, Bidyut; Das, Anand K.; Maiti, Sudipta (Frontiers in Physiology, 2013)
Amyloid beta (Aβ) is an extracellular 39-43 residue long peptide present in the mammalian cerebrospinal fluid, whose aggregation is associated with Alzheimer’s disease. Small oligomers of Aβ are currently thought to be the key to toxicity. However, it is not clear why the monomers of Aβ are non-toxic, and at what stage of aggregation toxicity emerges. Interactions of Aβ with cell membranes is thought to be the initiator of toxicity, but membrane-binding studies with different preparations of monomers and oligomers have not settled this issue. We have earlier found that thermodynamically stable Aβ monomers emerge spontaneously from oligomeric mixtures upon long term incubation in physiological solutions (Nag et al, JBC, 2011). Here we show that the membrane-affinity of these stable Aβ monomers is much lower than that of a mixture of small oligomers (containing dimers to decamers), providing a clue to the emergence of toxicity. Fluorescently labeled Aβ40 monomers show negligible binding to cell membranes of a neuronal cell line (RN46A) at physiological concentrations (250 nM), while oligomers at the same concentrations show strong binding within 30 minutes of incubation. The increased affinity most likely does not require any specific neuronal receptor, since this difference in membrane-affinity was also observed in a somatic cell-line (HEK 293T). Similar results are also obtained for Aβ42 monomers and oligomers. Minimal amount of cell death is observed at these concentrations even after 36 hours of incubation. It is likely that membrane binding precedes subsequent slower toxic events induced by Aβ. Our results a) provide an explanation for the non-toxic nature of Aβ monomers, b) suggest that Aβ toxicity emerges at the initial oligomeric phase, and c) provide a quick assay for monitoring the benign-to-toxic transformation of Aβ.